Endothelin‐converting enzyme 2 differentially regulates opioid receptor activity. (5th September 2014) - Gupta, A; Fujita, W; Gomes, I; Bobeck, E; Devi, L A
<x xml:space="preserve">Abstract</x> Background and Purpose Opioid receptor function is modulated by post‐activation events such as receptor endocytosis, recycling and/or degradation. While it is generally understood that the peptide ligand gets co‐endocytosed with the receptor, relatively few studies have investigated the role of the endocytosed peptide and peptide processing enzymes in regulating receptor function. In this study, we focused on endothelin‐converting enzyme 2 (ECE2), a member of the neprilysin family of metallopeptidases that exhibits an acidic pH optimum, localizes to an intracellular compartment and selectively processes neuropeptides including opioid peptides in vitro, and examined its role in modulating μ receptor recycling and resensitization. Experimental Approach The effect of ECE2 inhibition on hydrolysis of the endocytosed peptide was examined using thin‐layer chromatography and on μ opioid receptor trafficking using either elisa or microscopy. The effect of ECE2 inhibition on receptor signalling was measured using a cAMP assay and, in vivo, on antinociception induced by intrathecally administered opioids by the tail‐flick assay. Key Results The highly selective ECE2 inhibitor, S136492, significantly impaired μ receptor recycling and signalling by only those ligands that are ECE2 substrates and this was seen both in heterologous cells and in cells endogenously co‐expressing μ receptors with ECE2. We also found that ECE2 inhibition attenuated antinociception mediated only by opioid peptides that are ECE2 substrates. Conclusions and Implications These results suggest that ECE2, by selectively processing endogenous opioid peptides in the endocytic compartment, plays a role in modulating opioid receptor activity. Linked Articles This article is part of a themed section on Opioids: New Pathways to Functional Selectivity. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-2